Powered two-wheeler riding behavior and strategies to improve safety: A review - Shivam Singh Chouhan; Ankit Kathuria; Ravi Sekhar Chalumuri (Journal of Traffic and Transportation Engineering (English ed. Online))
Powered two-wheelers (PTWs) are considered as one of the risky means of transport as it is vulnerable to road crashes, which may lead to fatal injuries. Crash data revealed that the number of deaths caused by PTWs is significantly higher than any other road users. Literature reports that one of the major causes of high PTW crashes is the riding behavior of the users. Therefore, the present paper reviews existing literature related to factors affecting riding behavior. Several factors with different levels of influence on PTW riding behavior are explored in the paper. Further, safety strategies to improve PTW safety have been reported in the study by categorizing it based on risk factors, i.e., riding behavior, vehicle technology, and road infrastructure. The paper concludes with some of the major findings, i) riding behavior plays an essential role in improving PTW safety, ii) numerous research stated that riding behavior can be improved by enforcement and providing feedback about their riding behavior by profiling them into different categories, and iii) segregation of PTW traffic from other road users is reported to be an effective solution for increasing PTW safety in some developing countries. While a considerable amount of research related to riding behavior and PTW safety has been done, studies related to the impact of riding feedback on PTW riding behavior are scant. Further, it is suggested that future research should focus on the feasibility of advanced traffic management strategies, such as the segregation of PTWs from main traffic to reduce the conflict between vehicles.